(untitled) (Bangladesh Journal of Bioethics, 2020)
In the West, in countries such as the US and UK, people are equally encouraged to donate organs both to their relatives and nonrelatives. In practice, although family is the priority in the US and UK, anybody can donate organs to anyone else lawfully. Contrastingly, in Bangladesh, people are only legally allowed to donate organs for transplantation to close relatives. Bangladesh’s living organ transplantation policy and practice is in stark contrast with the Western secular biomedical perspective. In this artcile, I address that the notion of individual freedom and liberty in regard to the donation of organs for transplantation in the West is consistent with secular culture and biomedical perspectives, but such biomedical policy and practice is at odds with the Bangladeshi Muslim culture, socio-economic reality and biomedical perspective. As Bangladesh is a family-oriented collective society, the kinship relation and strong familial bonds may encourage relatives into donating organs to a patient. More than 20% of people still live below the poverty line, and the COVID-19 pandemic has pushed poor people into extreme poverty. The practice of allowing unrelated altruistic donors as is done in the West and Iran, or even in the special circumstance in Paksitan, the act of donating organs will comprehensievly increase organ trade in Bangladesh, which in turn will cause more harms than benefits. This study conludes that the government should uphold family-oriented biomedical policy and practice in Bangladesh until poverty is eliminated. It implies that patients who do not have close relatives, or whose poetntial relative donors are medically unsuitable for transplantations should wait for deceased organs for transplantation.